Nutrition and the brain - Edelson, Edward, 1932- (Encyclopedia of psychoactive drugs., 1988)
An analysis of how and why the types of foods we eat can affect normal brain functioning. Also discusses how diets can be manipulated to alter mental and emotional states in human beings.